PENGARUH TEKANAN KETAATAN, KEAHLIAN AUDIT DAN PENGALAMAN AUDIT TERHADAP AUDIT JUDGMENT DENGAN KOMPLEKSITAS TUGAS SEBAGAI PEMODERASI - Hazra Andryani; Endar Piturungsih; Lalu Furqan (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2019)
This study aims to analyze the effect of compliance pressure, audit expertise and audit experience on audit judgment and analyze the effect of compliance pressure, audit expertise and audit experience moderated by the complexity of the task of audit judgment. The number of respondents used in this study were 45 people who served as examiners at the West Nusa Tenggara Representative Office of the Supreme Audit Board (BPK). Data collection is done by survey method with data collection techniques using questionnaires. The data analysis technique is using moderation regression analysis. The results showed that obedience pressure did not affect audit judgment. While audit expertise and audit experience affect audit judgment. The complexity of the task does not strengthen the influence of obedience pressure on audit judgment. The task complexity variable also weakens the influence of audit expertise and audit experience on audit judgment.